Determination of Salicylic and Jasmonic Acids’s Median Lethal Concentration and its affecting in Tetranychus urticae Life cycle on Eggplant Leaves - Yusra Jamal Talib (University of Thi-Qar Journal of agricultural research, 2025)
The current study was conducted to determine the efficiency of salicylic acid concentrations 0, 0.5, 0.75 1mM and jasmonic acid concentrations 0, 5, 50 and 100μM in the adult T. urticae life stages. In addition to determining the median lethal concentration for both acids. This study was applied using the eggplant leaves under laboratory conditions. The results showed that the salicylic acid concentrations significantly influenced the adult longivity and life cycle of the mite T. urticae. The control treatment recorded the highest adult longivity and life cycle periods of 10.33 and 18.67 days, respectively. In contrast, the adult longivity decreased to 7 days when treated with a 0.75 mM concentration. While exposed to 0.5 mM of acid, the average life cycle period scored 12.67 days, significantly different from other salicylic acid concentrations. The lower acid concentrations were more effective in shortening the adult longivity and life cycle. The statistical study revealed the substantial impact of different concentrations of jasmonic acid on the adult longivity, egg stage period, and life cycle of the mite T. urticae. However, the control group registered the longest average adult longivity and the shortest egg stage period, with values of 10.33 days and 1 day, respectively. Moreover, jasmonic acid is most effective at decreasing the adult longivity, with the individual rearing on leaves that treated with 100µM of jasmonic acid reaching a minimum longivity of 6.33 days. It was also noted that the highest efficacy in prolonging the egg stage period resulted from 50 and 100µM jasmonic acid concentration, reaching a maximum of 2.67 days. Jasmonic acid. The lethal concentration of salicylic acid was found to be 1.53 mM, while the lethal value of jasmonic acid was reported to be 43.75 µM. As a result of the efficiency of these compounds in influencing pests, this study aimed to determine the several concentrations toxicity of salicylic acid and jasmunic acid in the two spotted spider mite T. urticae’s life stages. In addition to calculate the lethal concentrations of salicylic and jasmonic acids on adult Tetranychus urticae, two-spotted spider mites.